Saisir les dynamiques du conflit israélo-palestinien par les commentaires de vidéos et d’images sur Facebook - Simon Mastrangelo (Communiquer)
On social media, there is a very large number of audiovisual publications. This represents a considerable analytical material that can be studied from multiple angles. In addition to analyzing the contents themselves, taking into account comments related to audiovisual publications makes it possible to understand their reception. It also allows us to grasp the social dynamics that are being set up on online exchange platforms. Focusing on data collected on Facebook, this article shows how this methodology makes it possible to approach a topic as sensitive as the Israeli-Palestinian conflict. It is specifically aimed at presenting how the reference to Nazism serves as a means of delegitimizing the adversary, whether pro-Palestinian or pro-Israeli. The author observes that the comment sections on Facebook are above all spaces of self-assertion and exchange between people who share the same opinions. Little room is left for intergroup exchanges that could lead to the development of a true dialogue. Hate speech is frequently found and is sometimes based on references to Nazism. In the end, in-depth analysis of the comments makes it possible to delimit four types of discursive strategies of (de)legitimation.